Visualisasi Feminisme dalam Film Jelita Sejuba: Mencintai Kesatria Negara melalui Karakter Syarifah - Agnes Septiana; Achmad Sjafi'i (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2022)
Jelita Sejuba movie: Loving the Knights of the Country is examined in terms of visualizing the feminism of the film’s main character, namely Syarifah. Although not a feminist movie, there are indications of feminism features expressed by Syarifah’s character through visual language. The purpose of this research is to describe the visualization of feminism through shots, scenes, gestures, and dialogues. This qualitative descriptive study applies a purposive sampling method by selecting the most appropriate scene as a sample. The analysis of feminism in this study is seen from the scenes which contain the visualization of feminism. The results of this study conclude that feminism can be presented through shots in movies that summarize scenes, gestures, and dialogues. The visualization of feminism presented in the movie shows Syarifah’s attitude toward gaining the right to choose life according to her preferences.